(untitled) (Journal of Mathematical Study, 2017)
In this paper, we prove the decay and scattering in the energy space for nonlinear Schrödinger equations with regular potentials in R^d namely, i∂_tu+Δu-V(x)u+ λ|u|^p-1u=0. We will prove decay estimate and scattering of the solution in the small data case when 1+2d